Long‐term follow‐up of patients with short QT syndrome: clinical profile and outcome - El-Battrawy, Ibrahim; Liebe, Volker; Schimpf, Rainer; Tueluemen, Erol; Rudic, Boris; Lang, Siegfried; Wolpert, Christian; Zhou, Xiao-Bo; Akın, Ibrahim; Borggrefe, Martin (Journal of the American Heart Association, 2018)
BackgroundShort QT syndrome (SQTS) is a rare inheritable disease associated with sudden cardiac death. Data on long‐term outcomes of families with SQTS are limited.Methods and ResultsSeventeen patients with SQTS in 7 independent families (48% men; median age, 42.4 years; corrected QT interval, 324.9±40.8 ms) were followed up for 13.5±2.5 years. A history of sudden cardiac death was documented in 71% of families. A large number of them showed sudden cardiac deaths at a younger age, with a predominance of men (67%). Five patients had syncope (29%) and 9 (53%) had atrial fibrillation or atrial flutter. An SQTS‐related gene was found in 76% of the patients as follows: KCNH2 (SQTS 1) in 4, CACNA1C (SQTS 4) in 3, and CACNb2 (SQTS 5) in 6. Five patients (29%) received an implantable cardioverter‐defibrillator and 5 patients received long‐term prophylaxis with hydroquinidine. During follow‐up, 1 patient received an appropriate implantable cardioverter‐defibrillator shock attributable to ventricular fibrillation. The patient received no further implantable cardioverter‐defibrillator shocks after treatment with hydroquinidine.ConclusionsThe risk of sudden cardiac death in SQTS families is high. However, after appropriate risk assessment and individualized treatment options (hydroquinidine and/or implantable cardioverter‐defibrillator), the long‐term outcome is relatively benign when patients are seen at a reference center.
Gesehen am 20.08.2019